2006
DOI: 10.1079/ber2006419
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation in the interaction between three cereal aphids (Hemiptera: Aphididae) and wheat (Poaceae)

Abstract: The relative contributions of host plant, herbivore species and clone to variation in the interaction between cereal aphids and wheat were investigated using five clones each of three species, Rhopalosiphum padi (Linnaeus), Sitobion avenae (Fabricius) and Schizaphis graminum (Rondani), on seedlings of two cultivars of Triticum aestivum L. and one cultivar of Triticum durum Desf. More individuals and biomass of R. padi than of the other two species were produced on seedlings. The three wheat cultivars lost simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Yet, the relationship between host load and yield can be complex. For instance, the impact of aphids on crops can depend on crop type, aphid species, and the timing of infestation (Migui andLamb 2006, Rhainds et al 2012). Our exploration of two generic host load-yield relationships indicated that the type of relationship (linear vs. quadratic) mattered for the quantitative outcome of yield reduction, but less so for the qualitative outcome of the different scenarios (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the relationship between host load and yield can be complex. For instance, the impact of aphids on crops can depend on crop type, aphid species, and the timing of infestation (Migui andLamb 2006, Rhainds et al 2012). Our exploration of two generic host load-yield relationships indicated that the type of relationship (linear vs. quadratic) mattered for the quantitative outcome of yield reduction, but less so for the qualitative outcome of the different scenarios (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MacKay, Department of Entomology, University of Manitoba, and originally collected from cereal fields in southern Manitoba. The interactions of these clones with Canadian spring wheat were previously shown to be representative of the three aphid species (Migui and Lamb 2006). Aphids were reared in the laboratory on seedlings of common barley, Hordeum vulgare L. 'Argyle' (Poaceae) (Migui and Lamb 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The interactions of these clones with Canadian spring wheat were previously shown to be representative of the three aphid species (Migui and Lamb 2006). Aphids were reared in the laboratory on seedlings of common barley, Hordeum vulgare L. 'Argyle' (Poaceae) (Migui and Lamb 2006). Two species and three classes of commercial wheat from western Canada were investigated: T. aestivum, Canadian Western Red Spring (CWRS) and Canadian Prairie Spring (CPS), and T. durum, Canadian Western Amber Durum (CWAD).…”
Section: Methodsmentioning
confidence: 99%
“…Table S6). The estimated individual masses used for Collembola and Aphididae were 0.082 mg 64 and 4.5 mg 65 , respectively. Prey counts and biomasses were assessed for each sampling point and each session, except for Austria, for which only the first session was available.…”
Section: Methodsmentioning
confidence: 99%